Cuff Failure of Spiral-Filled Polyvinyl Chloride Endotracheal Tube Immediately after Tracheal Intubation Using a Channeled Videolaryngoscope (Pentax Airway Scope) - Koichi Nishikawa; Yoshihisa Fujita (Case Reports in Anesthesiology)
We report on a case of mechanical damage to the spiral-filled polyvinyl chloride endotracheal tube that occurred shortly after tracheal intubation using a channeled videolaryngoscope (Pentax airway scope). We also found this problem in two other cases among 350 neurosurgery patients over the past 5 years. Prior to intubation, we did not observe any defect in the cuff. However, the cuff could not be filled with air immediately after the intubation. Anesthesiologists should be aware that, during tracheal intubation using an airway scope, friction between the endotracheal tube and inner surface of the introducer might result in sudden rupture of the cuff.